KAJIAN PENAMBAHAN TEPUNG TAPIOKA DAN KUNING TELUR PADA PEMBUATAN BAKSO DAGING SAPI (Jurnal Teknologi Pangan, 2013)
ABSTRACT Meat ball is one of the emulsion food. Meat ball dough is oil in water emulsion made from fat and water mixed in colloid phase, with protein as emulsifier. Research aim on the effect of cassava flour (binder) and yolk addition  on the quality of meat ball has been conducted.  This research used Factorial  Randomized  Design  consisting  of  two  factors and  two  replications.  The  first  factor  is  yolk addition (20, 35, 50 and 65 grams) and the second factor is cassava flour addition (10, 12, 5, 15 and 17,5 gram). The  best treatment is combination of yolk 35 grams and cassava flour 12,5 gram. This meat  ball  product  has  emulsion  stability  (oil  separated)  :  1,24%  water  content  :  65,60%,  protein  : 10,29%, fat : 4,57%, texture value : 0,4465 mm/gr.dt. WHC value : 86,80%, taste score : 4,20, flavour score : 2,65 and texture score : 3,65, colour score : 2,68.Key words : meat ball, cassava flour, emulsion, yolk.